1999
DOI: 10.1109/50.769306
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber current sensors in high electric field environments

Abstract: Abstract-This paper analyzes the response of optical fiber current sensors that are subjected to high electric fields, such as fields encountered in gas-insulated systems. This paper shows that through the electrooptic (EO) Kerr effect, these fields can cause harmonic distortion of the measured ac current waveform. This harmonic distortion was confirmed experimentally. Also, this paper shows that it is possible to simultaneously measure both current and voltage waveforms and the phase between them using this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…In the earlier work, for the optical fiber current sensor with the current of 120 A, 26 loops of 15 cm diameter, and 636 nm of operating wavelength had shown the Faraday rotation of about 14 mrad, which gives (from Eq. (3)) the current sensitivity of 4.48 µrad/A for one loop [13], while in another report, the current sensitivity of about 5.58 µrad/A has been reported for the optical fiber current sensor [15]. The germanium concentration, the fiber structure, experimental conditions causing a small portion of linear polarization to be remained with the circular polarization can degrade the current sensitivity and these can be the cause of difference between current sensitivities of current sensors made with our single mode optical fiber and that of reported fibers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the earlier work, for the optical fiber current sensor with the current of 120 A, 26 loops of 15 cm diameter, and 636 nm of operating wavelength had shown the Faraday rotation of about 14 mrad, which gives (from Eq. (3)) the current sensitivity of 4.48 µrad/A for one loop [13], while in another report, the current sensitivity of about 5.58 µrad/A has been reported for the optical fiber current sensor [15]. The germanium concentration, the fiber structure, experimental conditions causing a small portion of linear polarization to be remained with the circular polarization can degrade the current sensitivity and these can be the cause of difference between current sensitivities of current sensors made with our single mode optical fiber and that of reported fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Twisting of optical fibers has been already used to enhance the current sensitivity of optical fibers [13][14][15]. In fact, it has been observed that in the spun fibers, sensitivity reaches the value for the ideal isotropic fiber [14].…”
Section: Current Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This added modulation (or noise) is owing to the additional electro-optic effect induced by the disturbing electric field. It was noted in [9] and [10] that the changes of the polarizability of the optical fiber material molecules was due to this disturbing electrical field, which in turn altered the phase and/or the amplitude of the modulated optical waves propagating in the fiber. Note that due to the small size of a typical Manuscript optical fiber diameter, practical and modest magnitude of modulating voltages applied to the unshielded fiber are sufficient to achieve significant noise (or modulation) [2], [3] in the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Another method employs electro-optical crystals. Here, changes in the refractive index proportional to E (Pockels effect) or to E 2 (Kerr effect) are used [17][18][19]. Such sensors, however, are hardly of practical use-one exception poses the application as voltage sensor for high-voltage power lines [20].…”
mentioning
confidence: 99%